2016
DOI: 10.15386/cjmed-527
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects induced by combined treatments of aqueous extract of propolis and venom

Abstract: Background and aimsBreast cancer is a heterogeneous disease and the leading cause of cancer mortality worldwide. Triple negative breast cancer (TNBC) is considered to be one of the most aggressive breast neoplasia due to failure of chemotherapy response. Thus, there is an urgent need of finding alternative therapies for TNBC. This study was designed to evaluate the synergistic effect induced by propolis and bee venom on luminal (MCF-7) and TNBC (Hs578T) cell lines.MethodsIn order to evaluate the synergistic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The authors also point to the synergy of BV with cisplatin [57], hesperidin and piperine [60], 5-fluorouracil and fluphenazine [37]. BV or melittin, alone or in combination with above mentioned chemotherapeutic agents, induced apoptosis in breast cancer cells, showed antiproliferative activity, and inhibited cell migration [34,66,74]. Tetiko glu et al [28] indicate the genotoxicity of BV to both breast cancer cells and physiological cells by the interaction of phosphorylated H2A histone family member (XγH2AX) and β-actin.…”
Section: Apoptosismentioning
confidence: 96%
“…The authors also point to the synergy of BV with cisplatin [57], hesperidin and piperine [60], 5-fluorouracil and fluphenazine [37]. BV or melittin, alone or in combination with above mentioned chemotherapeutic agents, induced apoptosis in breast cancer cells, showed antiproliferative activity, and inhibited cell migration [34,66,74]. Tetiko glu et al [28] indicate the genotoxicity of BV to both breast cancer cells and physiological cells by the interaction of phosphorylated H2A histone family member (XγH2AX) and β-actin.…”
Section: Apoptosismentioning
confidence: 96%
“…This showed that the combination of propolis-honey had higher anti-microbial activity than those individually utilized. Drigla et al [29] also showed the synergistic effect of propolis with other ingredients, where compound combinations and bee venom had higher anti-proliferative activity in breast cancer cells. This indicated that there was a synergistic effect among the compounds present in propolis.…”
Section: Synergistic Effectmentioning
confidence: 98%
“…Furthermore, a combination of propolis and bee venom showed a marked curative effect on OS produced by gamma radiation in rats 33 . Additionally, a combination treatment consisting of aqueous extract of propolis and bee venom induced synergistic antiproliferative effects in breast cancer cells 34 . Other synergistic effects have been investigated involving using mixtures of honey, propolis, pollen, and RJ to mitigate the toxic effects of insecticides in rats 35 .…”
Section: Introductionmentioning
confidence: 99%